EU law and international arbitration : managing distrust through dialogue - Papp, Konstanze von (London [England] : Hart Publishing, 2021)
"This timely book addresses the main areas of tension between EU law and international arbitration, looking at both commercial and investment treaty arbitration. It opens pathways for practical solutions based on communication between the different regimes. At the same time, it offers a sound theoretical basis that allows for addressing the core problem as normative conflict between legitimate public interests and the 'privatisation of justice'. The book is divided into five parts. It introduces key aspects of the overall tension between EU law and international arbitration, before setting out the theoretical framework that understands EU law, international commercial arbitration, and investment treaty arbitration as closed regimes. The author then addresses the core problem of finding the limits to contracting out of the EU legal regime, both on a jurisdictional and a substantive level. This is then linked to the question of trust-building in legal outcomes of the relevant regimes. The book concludes with a short summary and key theses. Combining a theoretical and normative with a more pragmatic approach to very topical issues, this book offers invaluable insights for academics and practitioners, private and public, commercial and investment treaty lawyers alike."--
Chapter 4: Building trust in legal outcomes of EU law and international arbitration -- I The challenges -- A The problem of legitimacy in a transnational context -- B Fundamental risk for the international legal system -- II Ensuring critical self-reflection through outward engagement -- A Institutionalised dialogue -- B Building structure through common concepts -- Chapter 5:Conclusion and key theses.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Arbitration, International -- European Union countries; International commercial arbitration -- European Union countries; European cooperation; International arbitration; Electronic books